Standardized Clinical Assessment and Management Plans (SCAMPs): Perspectives on a New Method to Understand Treatment Decisions and Outcomes in Immune Thrombocytopenia - Grace, Rachael F. (2013)
Modern evidence based guidelines in immune thrombocytopenia (ITP) are mostly based on expert opinion. Standardized clinical assessment and management plans (SCAMPs) are flexible, feedback-based practice guidelines that could be valuable for both managing patients with ITP and understanding treatment decisions and outcomes. At Boston Children’s Hospital, we have implemented a SCAMP for patients with newly diagnosed and persistent ITP. To develop the algorithm, a group of local ITP experts devised an initial guideline, which was then modified by the attending hematologists who care for ITP patients until consensus was reached. Since deviations from the algorithm are encouraged, all clinicians did not need to agree with all aspects of the algorithm. At each clinic visit, clinicians fill out data collection forms explaining practice deviations. The goals of this process are to decrease practice variation and resource utilization and learn from the outcomes and deviations that occur to continually improve our practice. SCAMPs are an innovative approach to improve quality of care in ITP.